Emergency management in the aesthetic medicine practice: a questionnaire to define the future of training in Italy - Spadotto, Lorenzo; Giaquinta, Samuel; Di Fronzo, Pasquale; Gambolò, Luca (Aesthetic Medicine, 2025)
Background: Out-of-hospital cardiac arrest is a critical condition with an average survival rate of around 10%, heavily influenced by the speed and competence of the intervention. Specific training for emergency management, such as BLSD (Basic Life Support and Defibrillation), is not mandatory for all physicians, including aesthetic doctors, who may encounter emergencies during outpatient treatments. Aim: This study developed and validated a questionnaire to assess aesthetic doctors’ preparedness emergency management, the availability of emergency devices in clinics, the level of experience with handling emergencies, and opinions on specific training for aesthetic doctors. Methods: A working group of aesthetic doctors developed the questionnaire after thoroughly reviewing the literature and current regulations. It was subsequently administered to a sample of 10 aesthetic doctors. Results: The evaluation by the participants showed a high alignment with the study’s objectives (average of 4.5 out of 5) and a high perceived usefulness for aesthetic medicine (average of 4.7 out of 5). The results indicate that 60% of the doctors had completed BLSD and ACLS/ALS (Advanced Cardiovascular Life Support/Advanced Life Support) courses, while 100% of the participants believe that BLSD should be mandatory. Additionally, 50% of the doctors had managed medical emergencies in the clinic, and 10% had dealt with a cardiac arrest. Conclusions: Despite the small sample size, the results suggest the need for mandatory training to improve patient safety. Sharing the questionnaire with scientific societies in aesthetic medicine and encouraging more colleagues to complete it could contribute to the broader adoption of these training practices.